24 A novel anti-hypertrophic pathway in cardiomyocytes regulated by the tumour suppressor mammalian STE20-like kinase 1 (Mst1). Issue 20 (23rd September 2011) - Maqsood, A; Reynolds-Khan, Y; Neyses, L; Oceandy, D
Abstract : The mammalian STE20-like kinase 1 (Mst1) is a pro-apoptotic kinase implicated in organ size control and tumour suppression. We have recently discovered that in the heart tumour suppressors may act as powerful inhibitors of myocardial hypertrophy. Here we have investigated the role of Mst1 in the inhibition of cardiomyocyte hypertrophy and have identified a novel downstream signalling pathway regulated by the cardiac Mst1. We used an adenovirus system to overexpress Mst1 in neonatal rat cardiomyocytes (NRCM). Mst1 overexpression completely abolished hypertrophy in cardiomyocytes in response to stimulation with 20 μM phenylephrine or 10% foetal bovine serum for 24 h as indicated by cell size measurements and expression of the hypertrophic marker BNP. Using a combination of bioinformatics and a luciferase reporter assay system we have identified a transcription repressor Yin Yang 1 (YY1) as a possible novel downstream target of Mst1. Cardiomyocytes overexpressing Mst1 were found to have an elevated level of cleaved YY1, which was translocated into the nucleus. YY1 has a caspase-3 cleavage site and the cleaved YY1 is active as a transcription repressor. We also found that caspase-3 activity was significantly increased in Mst1 overexpressing cells. In conclusion, our data showed that the tumour suppressor molecule Mst1 strongly inhibited cardiomyocyte hypertrophy. Mst1 displayed an opposing action in the cardiomyocytes compared to Mst2. Furthermore, these findings provide further evidence of an inter-relationship between regulation of tumour growth and cardiac hypertrophy.